Prospects of "Order Table" Infrastructure in Samarkand in Providing Employment and Increasing Economic Efficiency - Ibrokhim, Salamov; Sharifovna, Nazarova Maryam; Saloxiddinovna, Kazakova Zulaykho; Beknazarovich, Jonibekov Fakhriddin (European Journal of Life Safety and Stability (2660-9630), 2022)
In this scientific article, the prospects of the "order desk" infrastructure in Samarkand to ensure employment, food security, sustainable provision of citizens with agricultural products in case of emergency and increase economic efficiency, crop, livestock, veterinary, construction, joint Comparison of the results of scientific and practical economic analysis for 2020-2021 in the field of viticulture, horticulture, animal husbandry, beekeeping and other industries, descriptions of foreign experts and scientists on the relationship between enterprises and joint projects, the fruit and vegetable industry , foreign experts and scientists. In the activities of agricultural enterprises, organizations, infrastructure entities, farms, including diversified farms, life safety and other entities "Field-table", "Base-building object", "Field-consumer-consumer", "Field-consumer"; Problems and their solutions in the organization of infrastructure services such as "Veterinary and Livestock Complex", "Field-Livestock Complex", "Field Livestock Complex", definitions and changes in the field of small business and private entrepreneurship. Scientific-practical recommendations and proposals on private entrepreneurship. Advantages of the use of innovative techniques and technologies, profit from the sale of goods, the level of profitability of routes in the region and some districts, product quantity, quality, gross income, cost, production proposals. List of future and used sources.